Le bulletin nul : une forme de résistance à la normalisation de la vie politique (Paris, 1851-1870) - Vincent Huet (Amnis)
Parisians who deliberately chose not to answer yes nor no to questions asked in the plebiscites held in 1851, 1852 and 1870 – even though there were relatively few of them to do so – used that gesture to express their refusal to be asked anything by a power that they deemed illegitimate. Instead of abstaining from voting, they refused to accomplish their duty according to the norm decreed by the regime, and took advantage of the freedom of speech provided by the vote to oppose that power. In doing so, they subverted the legal political order that had been forced upon them – that of the universal vote for men, which was wholly reinforced by Louis-Napoléon Bonaparte after his coup. With that act, they indicted the will of both the power and its legalist opponents to normalise political life and to limit the political action of citizens to the sole vote, at the expense of a whole range of already well-experimented practices.